Pulsed Optical Emission from PSR 0656+14 - Shearer,A; Redfern,RM; Gorman,G; Butler,R; Golden,A; O'Kane,P; Beskin,G; Neizvestny,SI; Neustroev,VV; Plokhotnichenko,VL; Cullum,M (Astrophysical Journal Letters, 1997)
Using data collected with the Special Astrophysical Observatory (SAO) 6 m telescope and the University College Galway (UCG) Transputer Instrument for Fast Image Deconvolution (TRIFFID) imaging photometer, we show that the radio, X-ray, and gamma -ray pulsar PSR 0656+14 exhibits pulsed optical emission. We observed that the pulsed fraction was consistent with 100% and that the flux was higher than that expected from a thermal source. The magnitude of PSR 0656+14 in the B band was observed to be 25.1 +/- 0.3, consistent with previous CCD observations. The peak of the optical signal is at phase 0.2 compared to the radio and in phase with the weak gamma -ray pulse.